Ultra clean processing of semiconductor surfaces XI : selected, peer reviewed papers from the 11th international symposium on ultra clean processing of semiconductor surfaces (UCPSS), September 17-19, 2012, Gent, Belgium - Heyns, Marc; Mertens, Paul; Meuris, Marc (Trans Tech Publications Ltd., 2013)
This volume covers various aspects of ultra-clean technology for the large-scale integration of semiconductors. These include cleaning and contamination control in both front-end-of-line (FEOL) and back-end-of-line (BEOL) processing, as well as cleaning for semiconductor photo-voltaic applications. Also covered are studies of general topics such as particle removal using acoustic enhancement, the removal of metallic contamination, pattern collapse of fine flexible and fragile features, wetting and drying, contamination control and contamination metrology. The FEOL and BEOL contributions also t.
Keywords: Electrical engineering -- Congresses.; Semiconductors -- Surfaces -- Congresses.; elektronické knihy; electronic books